2020
DOI: 10.11113/ijbes.v7.n3.600
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phase Change Materials for Lifetime Heating of Buildings in Cold Climatic Conditions

Abstract: The study focuses on utilization of the solar insulation in buildings by means of thermal storage materials. During months of April to October, a significant part of solar gain was noticed in outer walls as well as in roof of the structure. Light weight modern construction materials have low thermal inertia so it stores less energy. The study focuses on the utilization of Phase Change Materials (PCM) for harnessing solar thermal energy for heating buildings. Various researches that show the effect of implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The specific heat capacity of the material, the quantity of the material, and the temperature change gradient all affect how much energy SHS systems can store. The amount of heat can be calculated by Equation (1) and Equation (2) [19]:…”
Section: Sensible Heat Storage (Shs)mentioning
confidence: 99%
“…The specific heat capacity of the material, the quantity of the material, and the temperature change gradient all affect how much energy SHS systems can store. The amount of heat can be calculated by Equation (1) and Equation (2) [19]:…”
Section: Sensible Heat Storage (Shs)mentioning
confidence: 99%
“…Therefore, they can be applied as a heat supplier when it incorporates building envelope under cold climate conditions [58]. It has been reported that PCMs can increase the thermal storage of the building envelope, which is usually constructed from materials with low thermal inertia [59]. Seong and Lim [60] numerically studied the thermal benefits of PCMs have different melting temperatures incorporated lightweight building envelope under weather conditions of Seol, Korea.…”
Section: Contribution Of Pcm To the Building Energymentioning
confidence: 99%